Arabic News Framing of Religious Activities in Indonesia and Malaysia During the Pandemic - Yoyo, Yoyo; Zaini, Abdul Razif; Yusroh, Yusroh; Ferawati, Ferawati; Mohd Hamidin, Norfaezah (Jurnal Al-Maqoyis, 2024)
This paper aims to analyse the framing of Arabic news media, namely Indonesia Al Youm and Aswaq Malaysia, regarding restrictions on religious activities during the pandemic. This qualitative research uses primary data on religious practices during COVID-19 in Indonesia Al-Youm and Aswaq Malaysia. In analysing framing media from Arabic newspapers, the paper proposed the theoretical concept of framing media by Pan and Kosicki. This paper found that Indonesia al-Youm's news related to restrictions on religious activities during COVID-19 is minimal. Therefore, media framing is limited and does not represent the media's ideology in reporting restrictions on religious activities. On the contrary, Aswaq Malaysia can provide detailed media framing regarding restrictions on religious activities during the pandemic. This is because the Malaysian government has gradually issued regulations on religious activity restrictions for each state in the Malaysian region. However, Aswaq's news framing regarding restrictions on religious activities sounds neutral and does not contain any expressive elements to attack certain parties.